Association of atherogenic index of plasma with early-onset post-stroke depression: a prospective study - Mingzhu Deng; Kangping Song; Guohua He; Wei Zhao; Wei Xu; Tieqiao Feng; Sufen Chen; Yangping Tong; Yanqing Fei; Zhen Wang; Fangyi Li (Frontiers in Psychiatry)
BackgroundThe atherogenic index of plasma (AIP) is a newly developed marker of lipids that has strong prognostic value in people with cardiovascular disease. Nevertheless, few studies concern the relationship between AIP and early-onset post-stroke depression (PSD).MethodsAfter two weeks of acute ischemic stroke (AIS), early-onset PSD was identified. The Hamilton Depression Scale-17 items (HAMD-17) was used to assess the severity of depression. Patients with HAMD-17 scores ≥7 were divided into an early-onset PSD group. Spearman rank correlation analysis was employed to evaluate the associations between AIP and HAMD scores across all patients. Logistic regression analysis was conducted to investigate the associations between the AIP and early-onset PSD. Receiver operating characteristic curve (ROC) analysis was used to determine the predictive value of the AIP for early-onset PSD.ResultsAmong the 667 recruited patients, a total of 225 (33.73%) patients were diagnosed with early-onset PSD. The AIP showed a positive correlation with the HAMD-17 scores (r=0.567, P<0.001). A binary logistic regression model demonstrated that the AIP (odds ratio [OR], 1.843; 95% confidence interval [CI] 1.650–2.558, P<0.001) was an independent factor for early-onset PSD. The AIP for early-onset PSD had an area under the curve (AUC) value of 0.785.ConclusionsOur study indicates that the AIP may serve as an independent risk factor for early-onset PSD, offering insights for the prevention and management of prognosis in affected patients.